Pemberdayaan Pemberdayaan Masyarakat Korban Angin Puting Beliung di Kabupaten Sumedang dan Kabupaten Bandung - Sutarman Sutarman; Lina Sukanti; Slamet Riyanto; Novi Irwansyah (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The aim of this research is to determine the impact of tornado victims in Ranca Ekek, Sumedang Regency and Cicalengka, Bandung Regency. Empowerment of tornado victims. The research method uses a qualitative approach that describes events in locations affected by tornadoes. Data collection techniques were interviews with several victims, RW administrators and RW administrators, observation at the location, photographing the condition of the places and houses of residents affected by the tornado. Literacy studies related to the tornado phenomenon include books and the internet. Conclusion The impact that occurred on the victims resulted in damage to people's houses and sales stalls on the side of the road so that they had no shelter to take shelter in and lost a place to sell. Empowerment of residents affected by tornadoes, consisting of 5 affected sub-districts, namely Rancaekek, Cicalengka and Cileunyi sub-districts, Bandung Regency, as well as Mangunraja and Jatinangor sub-districts, Sumedang Regency. Erected tents for around 121 residents, provided treatment to around 113 residents with minor injuries and 10 moderate injuries. In the future, the Regent of Sumedang and the Regent of Bandung will allocate assistance to the community so they can rebuild houses and kiosks for selling.